Narrow and twin-row plantings do not increase maize yield Siembras en hileras estrechas y mellizas no incrementan el rendimiento del maíz - Schmitt A.* (2020)
© 2020, Universidad Nacional de Colombia. All rights reserved.Reducing row space and sowing in twin rows of maize (Zea mays L.) allow more equidistant plant distribution at the same density. The objective of this research was to evaluate the effect of these two management practices on the nitrogen content of the index leaf, the leaf area index at silking, and the grain yield of maize at different plant densities. The experiment was carried out in Lages, Santa Catarina State University, in southern Brazil during the growing seasons 2016-2017 and 2017-2018. A split-plot arrangement of a randomized complete block design was used. Two plant densities (7 and 9 plants m-2) were distributed in the main plot, and five row spaces (0.4, 0.6, 0.8, 1.0 m and twin rows 0.6 m apart with 0.18 m between rows) were evaluated in split-plots. Physiological traits and grain yield were determined on the maize hybrid P30R50YH. The experiments were sown on 10/20/2016 and 10/21/2017. Kernel yields were higher at the plant density of 9 plants m-2 than at 7 plants m-2. The row space did not affect the nitrogen content of the index leaf, the crop leaf area index at silking, and the maize grain yield. The increment of plant density was more effective than the use of narrow and twin rows to enhance P30R50YH hybrid grain yield.